Assessment of waterlogging tolerance in tea genotypes through morpho-physiological and biochemical profiling - Md. Riyadh Arefin; Shitosri Mondal; Md. Fazle Rabbi; Hafsa Tasnim; Md. Alamgir Hossain; Md. Sabibul Haque; A. K. M. Golam Sarwar (PLoS ONE, 2026)
Tea is one of the major economic crops in Bangladesh, however, its productivity is severely constrained by waterlogging stress arising from erratic climatic changes. A significant knowledge gap persists regarding the morpho-physiological and biochemical determinants of waterlogging tolerance and post-stress recovery in tea, hindering the development of tolerant genotypes. Therefore, the present study aimed to investigate the integrated morpho-physiological and biochemical responses of tea genotypes under waterlogging stress to identify tolerant genotype(s) based on stress tolerance indices (STIs). Eight pre-screened tea genotypes—P/LAL/08/23, P/LAL/08/62, P/LAL/09/116, P/AFN/11/35, P/AFN/11/46, P/OTI/31, P/AFN/13/90, P/AFN/11/31, with two control clones, BT2 (popular variety) and TV9 (waterlogging-tolerant variety), were evaluated using 23 morpho-physiological and biochemical parameters maintaining a two-factorial completely randomized design experiment. One set of tea genotypes was exposed to a 14-day waterlogging phase, followed by a 14-day recovery phase (total 28 days of stress), while another set of plants was maintained under control (non-stress) conditions, for the same period, to calculate STIs. Root fresh weight (RFW), leaf number (NL), net photosynthesis ( Pn ), transpiration rate ( E ), stomatal conductance ( g s ), relative leaf water content (RWC), and absolute growth rate (AGR) were significantly decreased under waterlogging condition compared to the control. Leaf chlorophyll a (CHA), chlorophyll b (CHB), and total carotenoids (CRTN), were reduced under stress, whereas proline content (of leaf: PRLF and root: PRRT), total antioxidant activity (of leaf: TACL and root: TACR), and lipid peroxidation (of leaf: LOPL and root: LPOR) increased as a part of adaptive responses. The traits such as RFW, NL, Pn , E , g s , RWC, AGR, CHA, CHB, CRTN, and LPOL, were detected as most influential at both phases of stress conditions from principal component analysis. Ultimately, the P/AFN/13/90 was identified as the most waterlogging-tolerant genotype, exhibiting higher STIs for maximum traits during both the waterlogging and recovery phases.